(untitled) (Research, Society and Development, 2022)
Currently, the use of biomaterials in the health area is constantly evolving. It is known that the development of materials using chitosan, a biocompatible polymer with antimicrobial action, associated with essential oils, a natural substance with numerous biological and antimicrobial properties, has been studied. Therefore, we sought to verify the literature studies related to the antimicrobial activity of chitosan-based biomaterials associated with different essential oils, aimed at the health area. A literature review was carried out in the PubMed and Science Direct databases, from 2018 to 2022, using the descriptors "Chitosan" AND "Essential Oil" AND "Antimicrobial Activity" AND "Dressing". A total of 305 articles were found in the database search, of which eight articles were included in the study, in which it was possible to divide them according to the final product into: (1) film; (2) cryogel, and; (3) nanofibrous scaffolds. Antimicrobial analysis techniques included an agar diffusion test and minimal inhibitory/microbicide concentration. It was possible to verify that the chitosan-based biomaterials alone already showed inhibition of the microbial strains tested and, when associated with essential oils, there was an increase in the action against the strains, making them promising for biomedical applicability.